Multi-Modal Analysis of Satellite Cells Reveals Early Impairments at Pre-Contractile Stages of Myogenesis in Duchenne Muscular Dystrophy - Sophie Franzmeier; Shounak Chakraborty; Armina Mortazavi; Jan B. Stöckl; Jianfei Jiang; Nicole Pfarr; Benedikt Sabass; Thomas Fröhlich; Clara Kaufhold; Michael Stirm; Eckhard Wolf; Jürgen Schlegel; et al. (Cells, 2025)
Recent studies on myogenic satellite cells (SCs) in Duchenne muscular dystrophy (DMD) documented altered division capacities and impaired regeneration potential of SCs in DMD patients and animal models. It remains unknown, however, if SC-intrinsic effects trigger these deficiencies at pre-contractile stages of myogenesis rather than resulting from the pathologic environment. In this study, we isolated SCs from a porcine DMD model and age-matched wild-type (WT) piglets for comprehensive analysis. Using immunofluorescence, differentiation assays, traction force microscopy (TFM), RNA-seq, and label-free proteomic measurements, SCs behavior was characterized, and molecular changes were investigated. TFM revealed significantly higher average traction forces in DMD than WT SCs (90.4 ± 10.5 Pa vs. 66.9 ± 8.9 Pa; p = 0.0018). We identified 1390 differentially expressed genes and 1261 proteins with altered abundance in DMD vs. WT SCs. Dysregulated pathways uncovered by gene ontology (GO) enrichment analysis included sarcomere organization, focal adhesion, and response to hypoxia. Multi-omics factor analysis (MOFA) integrating transcriptomic and proteomic data, identified five factors accounting for the observed variance with an overall higher contribution of the transcriptomic data. Our findings suggest that SC impairments result from their inherent genetic abnormality rather than from environmental influences. The observed biological changes are intrinsic and not reactive to the pathological surrounding of DMD muscle.